Period‐specific mean annual hospital volume of radical cystectomy is associated with outcome and perioperative quality of care: a nationwide population‐based study. (22nd April 2019) - Liedberg, Fredrik; Hagberg, Oskar; Aljabery, Firas; Gårdmark, Truls; Hosseini, Abolfazl; Jahnson, Staffan; Jancke, Georg; Jerlström, Tomas; Malmström, Per‐Uno; Sherif, Amir; Ströck, Viveka; Häggström, Christel; et al.
Abstract : Objective: To investigate the association between hospital volume and overall survival (OS), cancer‐specific survival (CSS), and quality of care of patients with bladder cancer who undergo radical cystectomy (RC), defined as the use of extended lymphadenectomy (eLND), continent reconstruction, neoadjuvant chemotherapy (NAC), and treatment delay of <3 months. Patients and Methods: We used the Bladder Cancer Data Base Sweden (BladderBaSe) to study survival and indicators of perioperative quality of care in all 3172 patients who underwent RC for primary invasive bladder cancer stage T1–T3 in Sweden between 1997 and 2014. The period‐specific mean annual hospital volume (PSMAV) during the 3 years preceding surgery was applied as an exposure and analysed using univariate and multivariate mixed models, adjusting for tumour and nodal stage, age, gender, comorbidity, educational level, and NAC. PSMAV was either categorised in tertiles, dichotomised (at ≥25 RCs annually), or used as a continuous variable for every increase of 10 RCs annually. Results: PSMAV in the highest tertile (≥25 RCs annually) was associated with improved OS (hazard ratio [HR] 0.87, 95% confidence interval [CI] 0.75–1.0), whereas the corresponding HR for CSS was 0.87 (95% CI 0.73–1.04). With PSMAV as a continuous variable, OS was improved for every increase of 10 RCs annually (HR 0.95, 95% CI 0.90–0.99). Moreover, higher PSMAV was associated with increased use of eLND, continent reconstruction and NAC, but also more frequently with a treatment delay of >3 months after diagnosis. Conclusions: The current study supports centralisation of RC for bladder cancer, but also underpins the need for monitoring treatment delays associated with referral.